The Philosophical Background and the Adventures of Religious Studies:: The Case of Greece - Panagopoulou-Koutnatzi, Fereniki; Arabatzis, Georgios (Conatus - Journal of Philosophy, 2023)
The teaching of Religious Studies in Greece has always been the subject of intense debate and controversy. The case law of the Council of State mandates a denominational course, allowing exemption only on the grounds of religious conscience. The Supreme Administrative Court even considered the introduction of a compulsory Religious Studies course for all students to be unconstitutional. In this sense, the Religious Studies course in Greece is seen as outdated, and an increasing number of students are seeking to be exempt from it. In a recent case, the Council of State, in an attempt to depart from its previous case law on the exemption, essentially referred the decision on the matter in question to the Greek Data Protection Authority, which was requested to give its opinion on the status of the currently applicable exemption. In the context of this contribution, we argue that: a) The Council of State erred in its approach of shifting the burden of this decision to the Data Protection Authority. b) These issues should not be decided by the courts or independent authorities but by the democratically legitimized legislature. c) Religious knowledge is an indispensable element of education and, as such, the Religious Studies course should have an encyclopedic, rather than a narrowly developed denominational character and remain compulsory for all pupils.